ANALYSIS OF THE INFLUENCE OF MARKET ORIEN-TATION AND KNOWLEDGE MANAGEMENT ON COM-PETITIVE ADVANTAGE - M Rizal Maulana; R Deni Muhammad Danial; Kokom Komariah (Politeknik Negeri Bengkalis, 2022)
This research will focus on the SME creative industry, especially the craft sub-sector. In general, the craft industry must be able to produce quality products at competitive prices as their competitive advantage. From every fact that occurs in the field, the products offered by Craft MSMEs in Sukabumi Regency generally have high selling prices. This is because local craft products are made using human power and hands (handmade). Thus, most handmade products are not sold in large quantities and the price makes these products expensive. This study aims to determine the effect of market orientation and knowledge management on competitive advantage. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique used by the researcher is the saturated technique, namely a number of 35 craft SMEs in Sukabumi Regency. The data analysis technique used is multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient and partial test (t test). The results of the study using the t test showed that market orientation (X1) had a significant effect on competitive advantage (Y) and knowledge management (X2) had a significant effect on competitive advantage (Y). The contribution of market orientation and knowledge management variables to competitive advantage is 78%. While the remaining 22% is influenced by other variables outside this regression equation or variables that are not examined